Design of Triple-band Dipole-type Antenna with Dual-band Artificial Magnetic Conductor Structure - Abu, Maisarah; A. Rahim, Mohamad Kamal; Ayop, Osman; Zubir, Farid (2011)
A design of dual-band high-impedance surface called Artificial Magnetic Conductor (AMC) is presented. The AMC is designed to resonate at 0.92GHz and 2.45GHz. In this paper also, the design parameters that influence the AMC frequencies are discussed. The designed AMC then is incorporated with the designed triple-band printed dipole antenna (operating at 0.92GHz, 2.45GHz and 5.8GHz). Here, the performance of the dipole antenna with 2 and 4 unit cells of 0.92GHz and 2.45GHz AMC ground plane are presented. The reported results show that, by applying the AMC structure as a ground plane for the printed dipole antenna, the gain of the dipole antenna can be increased due to the attracting feature of the AMC surface that provide in-phase reflected waves with the incident waves.